Avalanche boron fusion by laser picosecond block ignition with magnetic trapping for clean and economic reactor. (11th October 2016) - Hora, H.; Korn, G.; Eliezer, S.; Nissim, N.; Lalousis, P.; Giuffrida, L.; Margarone, D.; Picciotto, A.; Miley, G.H.; Moustaizis, S.; Martinez-Val, J.-M.; Barty, C.P.J.; et al.
Abstract : Measured highly elevated gains of proton–boron (HB11) fusion (Picciotto et al., Phys. Rev. X4, 031030 (2014)) confirmed the exceptional avalanche reaction process (Lalousis et al., Laser Part. Beams32, 409 (2014); Hora et al., Laser Part. Beams33, 607 (2015)) for the combination of the non-thermal block ignition using ultrahigh intensity laser pulses of picoseconds duration. The ultrahigh acceleration above $10^{20}~\text{cm}~\text{s}^{-2}$ for plasma blocks was theoretically and numerically predicted since 1978 (Hora, Physics of Laser Driven Plasmas (Wiley, 1981), pp. 178 and 179) and measured (Sauerbrey, Phys. Plasmas3, 4712 (1996)) in exact agreement (Hora et al., Phys. Plasmas14, 072701 (2007)) when the dominating force was overcoming thermal processes. This is based on Maxwell's stress tensor by the dielectric properties of plasma leading to the nonlinear (ponderomotive) force $f_{\text{NL}}$ resulting in ultra-fast expanding plasma blocks by a dielectric explosion. Combining this with measured ultrahigh magnetic fields and the avalanche process opens an option for an environmentally absolute clean and economic boron fusion power reactor. This is supported also by other experiments with very high HB11 reactions under different conditions (Labaune et al., Nature Commun.4, 2506 (2013)).